Real-world use of mycophenolate mofetil in inflammatory bowel disease: Results from the ENEIDA registry. Issue 5 (May 2022) - Hernández-Camba, A.; Arranz, L.; Vera, I.; Carpio, D.; Calafat, M.; Lucendo, A.J.; Taxonera, C.; Marín, S.; Garcia, M.J.; Marín, G. Suris; Rodríguez, E. Sánchez; Carbajo, A.Y.; et al.
Abstract: Background: Studies to evaluate the use of mycophenolate mofetil (MMF) in inflammatory bowel disease (IBD) are limited after the appearance of biological treatments. Aims: Our primary objective was to evaluate the effectiveness and safety of MMF in IBD. Methods: IBD patients who had received MMF were retrieved from the ENEIDA registry. Clinical activity as per the Harvey‐Bradshaw Index (HBI), partial Mayo score (pMS), physician global assessment (PGA) and C-reactive protein (CRP) were reviewed at baseline, at 3 and 6 months, and at final follow-up. Adverse events and causes of treatment discontinuation were documented. Results: A total of 83 patients were included (66 Crohn's disease, 17 ulcerative colitis), 90% of whom had previously received other immunosuppressants. In 61% of patients systemic steroids were used at initiation of MMF, and in 27.3% biological agents were co-administered with MMF. Overall clinical effectiveness was observed in 64.7% of the population. At the end of treatment, 45.6% and 19.1% of subjects showed remission and clinical response, respectively. MMF treatment was maintained for a median of 28.9 months (IQR: 20.4–37.5). Conclusion: Our study suggests, in the largest cohort to date, that MMF may be an effective alternative to thiopurines and methotrexate in IBD.